Pengaruh pemahaman tentang peraturan perpajakan, persepsi efektifitas sistem perpajakan dan tingkat kepercayaan sistem pemerintahan dan hukum terhadap kemauan membayar pajak wajib pajak orang pribadi yang melakukan pekerjaan bebas - Fitriana, Sylvia; Ilham, Elfi; ', Zulbahridar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to examine empirically the effect of understanding of tax rules, the perception of the effectiveness of the tax system, and the level of confidence in the government system and law against the willingness to pay taxes on individual taxpayers who do the work free.The sample used in this study were selected from a population that is an individual taxpayer who has a work free in the Kantor Pelayanan Pajak Pratama Senapelan Pekanbaru. The sample was determined by the method of purposive random sampling. From population of taxpayers, which meets the criteria of the sample is 95 taxpayers. The Method of analysis used in this study is multiple linear regression with SPSS version 17.The results of this study showed that empirically the effect of understanding of tax rules, the perception of the effectiveness of the tax system, and the level of confidence in the government system and law simultaneously shown to significantly influence the willingness to pay taxes individual taxpayers who do the work free. The effect of understanding of tax rules on willingness to pay showed positive β1 coefficient was 0.490, with a significance of 0.000 (Significant) <0.05. Then the perception of the effectiveness of the tax system on the willingness to pay taxes showed positive β2 coefficient of 0.472, with a significance 0.040 (Significant) <0.05. Meanwhile, in partial the level of confidence in the government system and law against willingness to pay taxes have no effect as indicated by positive β3 coefficient of 0.156, with a significance of 0.106 (Not Significant)> 0.05.Keywords: the effect of understanding of tax rules, the perception of the effectiveness of the tax system, the level of confidence in the government system and law, willingness to pay.